The problem of governance - Jennifer Brick Murtazashvili (Frontiers in Political Science, 2025)
Shadi Hamid’s The Problem of Democracy makes a compelling case for focusing on government over governance. Hamid’s offers a view of a restrained American foreign policy in the Middle East that avoids falling into the trap of a crass isolationism or an overbearing imposition of liberalism. For all its insight, this essay makes a case that governance remains especially significant to promote peace and prosperity in fragile states. It also argues that minimalist democracy, where attempted, has not necessarily lived up to the promise Hamid sees for it.